Effect of Faculty Diversity on Minority Student Populations Matching into Orthopaedic Surgery Residency Programs. Issue 1 (6th January 2023) - Levy, Kenneth H.; Gupta, Arjun; Murdock, Christopher J.; Marrache, Majd; Beebe, Kathleen S.; Laporte, Dawn M.; Oni, Julius K.; Aiyer, Amiethab A.
Abstract : Background: Greater faculty diversity within orthopaedic residency programs has been associated with an increased application rate from students of similarly diverse demographic backgrounds. It is unknown whether these underrepresented student populations have an equitable likelihood of being highly ranked and matching at these programs. Thus, we sought to evaluate the relationship between faculty and resident diversity, with a specific focus on sex, racial/ethnic groups that are underrepresented in medicine (URiM), and international medical graduates (IMGs). Methods: The American Orthopaedic Association's Orthopaedic Residency Information Network database was used to collect demographic data on 172 US residency programs. Linear regression analyses were performed to determine the relationship between the proportion of female or URiM attendings at a program and the proportion of female, URiM, or IMG residents or top-ranked applicants (≥25 rank). URiM was defined as "racial and ethnic populations that are underrepresented in the medical profession relative to their numbers in the general population." Results: A mean of 13.55% of attendings were female and 14.14% were URiM. A larger fraction of female attendings was a positive predictor of female residents (p < 0.001). Similarly, a larger percentage of URiM attendings was a positive predictor of URiM residents (p < 0.001), as well as of URiM (p < 0.001) and IMG (p < 0.01) students being ranked highly. There was no significant association between URiM attendings and female residents/overall top-ranked applicants, or vice versa. Conclusions: Residency programs with more female attendings were more likely to match female residents, and programs with more URiM attendings were more likely to highly rank URiM and IMG applicants as well as match URiM residents. Our findings indicate that orthopaedic surgery residencies may be more likely to rank and match female or URiM students at similar proportions to that of their faculty. This may reflect minority students preferentially applying to programs with more diverse faculty because they feel a better sense of fit and are likely to benefit from a stronger support system. Level of Evidence: III.